Supply Chain Climate Exposure. Issue 1 (2nd January 2023) - Hall, Greg; Liu, Kate; Pomorski, Lukasz; Serban, Laura
Abstract : We propose an intuitive measure of supply chain climate risks, reflecting the fact that even a green company may have material climate exposure if its customers or suppliers face climate risks. Our measure captures price movements around climate news better than traditional climate data and shows performance patterns consistent with re-pricing of climate risks. The metric is more suitable for risk measurement than scope 3 emissions and requires raw data that is broadly accessible for large cross-sections of stocks and is of higher quality than currently available scope 3 data. We discuss applications for both portfolio and corporate decision-making.